Phenogenetics of cortical granule dynamics during zebrafish oocyte-to-embryo transition - García-Castro, Priscila; Giambó-Falian, Isabella; Carvacho, Ingrid; Fuentes, Ricardo (Frontiers in Cell and Developmental Biology, 2025)
Fertilization is a critical process in sexual reproduction that involves the fusion of a capacitated sperm with a mature oocyte to form a zygote. Polyspermy, the fertilization of an oocyte by multiple sperm, leads to polyploidy and embryo lethality. Mammalian and non-mammalian oocytes have evolved mechanisms to prevent polyspermy, including fast and slow blocks. The fast block comprises membrane depolarization post-sperm fusion, temporarily preventing additional sperm fusion. The slow block, triggered by cortical granule (CG) exocytosis, involves the release of proteins that modify the zona pellucida to form a permanent barrier, avoiding the fertilization by additional sperm. The evidence shows that immature oocytes often fail to prevent polyspermy due to ineffective CG exocytosis, attributed to impaired intracellular calcium increases, lower content of this ion, and incomplete CG migration. The study of how genetic variations lead to observable phenotypes (phenogenetics) during the oocyte-to-embryo transition, have identified several maternal-effect genes in zebrafish involved in CG behavior. These genes regulate various stages of CG biology, including biosynthesis, maturation, and exocytosis. Mutations in these genes disrupt these processes, highlighting the maternal genetic control over CG properties. Zebrafish has emerged as a pivotal model for understanding the evolving genetic regulation and molecular mechanisms underlying CG biology, providing valuable insights into fertility and early embryonic development.